2019
DOI: 10.1002/mgg3.1039
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing in Marfan syndrome: Value of standard screening questionnaires

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: A high prevalence of sleep disordered breathing (SDB) has been reported in persons with Marfan syndrome (MFS), a single gene disorder of connective tissue resulting in premature death from aortic rupture. The bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…A previous study demonstrated that the proportion of snoring breaths during sleep was a predictor of OSA in the general population [ 13 ]. Our study confirms this finding in persons with MFS, a genetic disorder characterized by aortic pathology [ 4 , 14 , 15 ] and sleep disordered breathing [ 1 3 ]. Our results further reveal that a 1-unit increase in snoring breaths percentage confers a 5% higher likelihood of OSA, and that a 10-unit increase in snoring breaths percentage associates with a 1 mm increase in aortic root diameter.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study demonstrated that the proportion of snoring breaths during sleep was a predictor of OSA in the general population [ 13 ]. Our study confirms this finding in persons with MFS, a genetic disorder characterized by aortic pathology [ 4 , 14 , 15 ] and sleep disordered breathing [ 1 3 ]. Our results further reveal that a 1-unit increase in snoring breaths percentage confers a 5% higher likelihood of OSA, and that a 10-unit increase in snoring breaths percentage associates with a 1 mm increase in aortic root diameter.…”
Section: Discussionsupporting
confidence: 88%
“…Thirty consecutive MFS patients who reported habitual snoring were recruited from the Johns Hopkins Vascular Connective Tissue Disorders Clinic and the Marfan Foundation. Participants completed a packet of sleep disordered breathing questionnaires including the STOP-BANG, Berlin questionnaire and the Epworth sleepiness scale (ESS) [ 1 , 8 , 9 ], and also provided contemporaneous aortic information verified with their medical records. All participants underwent overnight in-laboratory polysomnography, but one recording was excluded because participant’s sleep time was less than 2 h, thus data were not adequate for our analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated accurate OSA screening in persons with MFS who had home sleep studies using the STOP-BANG questionnaire. 33 As shown in this study, screening with the STOP-BANG questionnaire could serve as a simple means to stratify MFS persons for sleep phenotypes that might impact cardiovascular status. We do not believe that a high OSA risk finding with the STOP-BANG replaces a valid sleep study; instead we believe that this screening approach may provide a persuasive rationale for obtaining formal sleep studies in patients with MFS who present with atypical symptoms.…”
Section: Discussionmentioning
confidence: 80%
“…[7][8][9][10][11] A mutation in the recessive FBN1 gene-a component of elastic and nonelastic tissues-is a typical finding in MFS; however, some patients may lack the gene completely resulting in severe signs and symptoms. 12,13 Up to 10% of people with the MFS phenotype do not have the FBN1 mutation but have alterations in the transforming growth factor-beta receptor 2 (TGFBR2) and TGFBR1. 13 These mutations are linked to two other syndromes: Loeys-Dietz syndrome (LDS) or familial thoracic aortic aneurysm (FTAA) syndromes; some experts believe patients with MFS phenotype should be treated as LDS, which has severe complications.…”
Section: Pathophysiologymentioning
confidence: 99%